Komposisi Kimia Baby Fish Nila Larasati (Oreochromis niloticus) Pada Berbagai Umur Panen dalam Sistem Akuaponik: Chemical Composition of Baby Fish Tilapia (Oreochromis niloticus) Harvested in Different Periods Reared Under Aquaponic System - La Ode Abdul Rajab Nadia; Laode Muhamad Hazairin Nadia; Rosmawati Rosmawati; Wa Ode Piliana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Baby fish tilapia is mostly consumed by society in fried the fish and crispy forms, but the information on the nutritional composition of the fish is limited. The objective of the present study was to evaluate the chemical composition and fatty acids of baby fish tilapia harvested in different periods reared under aquaponic system. The research was conducted in factorial design with single factor namely different harvesting periods (14 days, 21 days, 28 days, and 35 days). The parameters measured were morphometric (body weight, total length and body length), chemical composition, and fatty acids. The results showed that the body weight affected the chemical composition. Statistical analysis showed that the proximate analysis was significantly different among the treatments (p<0.05). The highest saturated fatty acid (SAFA) and polyunsaturated fatty acid (PUFA) was palmitate (C6:0) dan linoleat (C18:2n6) respectively obtained at fish harvested in 14 days.